Fluorogenic and Bioorthogonal Modification of RNA Using Photoclick Chemistry - Katja Krell (Biomolecules, 2020)
A bromoaryltetrazole-modified uridine was synthesized as a new RNA building block for bioorthogonal, light-activated and postsynthetic modification with commercially available fluorescent dyes. It allows “photoclick”-type modifications by irradiation with light (300 nm LED) at internal and terminal positions of presynthesized RNA with maleimide-conjugated fluorophores in good yields. The reaction was evidenced for three different dyes. During irradiation, the emission increases due to the formation of an intrinsically fluorescent pyrazoline moiety as photoclick product. The fluorogenecity of the photoclick reaction was significantly enhanced by energy transfer between the pyrazoline as the reaction product (poor emitter) and the photoclicked dye as the strong emitter. The RNA-dye conjugates show remarkable fluorescent properties, in particular an up to 9.4 fold increase of fluorescence, which are important for chemical biology and fluorescent imaging of RNA in cells.